Developments in semi-submersible floating foundations supporting wind turbines: A comprehensive review. (July 2016) - Liu, Yichao; Li, Sunwei; Yi, Qian; Chen, Daoyi
Abstract: Semi-submersible foundation, as one of the most feasible platform supporting the floating offshore wind turbine, is developing at a fast pace with the offshore wind turbines moving to deep waters (water depth range: 50–300 m). This paper presents a rather comprehensive review on the semi-submersible foundation. At first, this paper reviews the design of semi-submersible foundations, which includes both the conceptual design and the projects currently under operation. Afterwards, a number of simulation tools employed in previous researches to investigate the dynamics of semi-submersible foundations are summarized. In detail, wind-wave basin tests and numerical simulations concerning the dynamic responses of the semi-submersible foundation under the excitations of wind-wave loads are included. As for basin test, key techniques for simulating the realistic wind-wave fields and for accurately modeling different part of a floating wind turbine are reviewed. As for numerical studies, the free-vortex wake model is outlined, which was introduced to overcome the defects of the conventional blade element momentum theory used commonly in estimating the wind load on the wind turbine blades. Additionally, a novel technique coupling a three-dimensional flow solver EllipSys3D with FLEX5 is discussed.